Kode Etik Guru dan Implikasinya Terhadap Hubungan Guru dan Siswa dalam Proses Pembelajaran - Della Sari Manalu; Dorlan Naibaho (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Education plays a vital role in shaping the character and quality of human resources, with teachers as key figures who serve as educators, mentors, and role models for students. One crucial factor that significantly impacts a teacher's success is the application of the professional code of ethics, which serves as a moral and professional guide in carrying out their duties. This code of ethics governs the attitudes, behaviors, and responsibilities of teachers toward students, the community, and colleagues. The implementation of the code of ethics not only ensures the integrity and professionalism of teachers but also influences the teacher-student relationship, ultimately fostering a conducive learning environment.The teacher's code of ethics functions as a moral guideline that regulates the behavior, attitudes, and responsibilities of teachers toward students, society, and fellow colleagues. The application of this code of ethics greatly impacts the relationship between teachers and students in the learning process. This study aims to analyze the application of the teacher's code of ethics and its effects on interactions that occur in the classroom. A qualitative approach was used in this research to explore the experiences and perspectives of both teachers and students regarding the implementation of the code of ethics in teaching. The results indicate that the application of the code of ethics strengthens the professional relationship between teachers and students, creates a fair, inclusive, and respectful learning environment. The teacher's code of ethics encourages teachers to act with fairness, maintain integrity, and uphold confidentiality, which positively affects the quality of learning. However, challenges in its implementation, such as balancing emotional closeness and professionalism and ensuring objectivity in assessment, must still be addressed. Overall, consistent implementation of the code of ethics can foster healthy, productive relationships and support the creation of a more effective and dignified learning process.